ANALISIS PENGGUNAAN CDI DIGITAL HYPER BAND DAN VARIASI PUTARAN MESIN TERHADAP TORSI DAN DAYA MESIN PADA SEPEDA MOTOR YAMAHA JUPITER MX TAHUN 2008 - Purnomo, Heri (Jurnal Nosel, 2012)
The purpose of this research is (1) Analyzing the use of CDI digital hyper band to the torque and engine power on the motorcycle Yamaha Jupiter MX in 2008. (2) Analyze the variations of engine round to the torque and engine power on the motorcycle Yamaha Jupiter MX 2008. This research has done in AHASS TARUNA MOTOR SPORT WORKSHOP that located in Jl. Bhayangkara no. 78 solo using DYNOJET. This research uses experimental methods. The sample in this research is a motorcycle Yamaha Jupiter MX in 2008 with 2S6439296 engine number and chassis number MH32S60058K439042. Based on the results of the research can be summed up: (1) Increasing round of engine could raise torque and power produced at the axle to the maximum. The round of engine a having reached a maximum of torque and power making torque and power that is produced at the axle to decline. (2) Using of CDI digital hyper band does not increase the maximum torque and power produced at the axle. (3) Using of digital CDI hyper band can increase round maximum machine , as that of 1500 rpm from round maximum machine that can be attained by standard CDI. Increasing round maximum machines increases the speed maximum that can be attained by a vehicle .